Konsep Pendidikan Anak Pada Kisah Ibu Musa dalam Al-Qur’ân - Moh. Toriqul Chaer (CONTEMPLATE: Jurnal Ilmiah Studi Keislaman, 2020)
This article discusses the story of Musa Mother in the Tafsir al-Misbah with regard to the concept of education. Tafsir al-Misbah using maudhȗ'i method with his emphasis on problems occurred in the society (al-adabî al-ijtimâi). search history Yokabed rely on encyclopedias, history books of the old testament as well. This is because the story of the Yokabed is not depicted as a whole in the al-Qur'ân. From the results of the study, revealed some findings as follows: first, the story of the mother of Moses. Not described completely in al-Qur'ân. The search effort is required on the history books, encyclopedias and also the Gospel, in the old testament. Second, the story of the mother of Moses there was educational value Faith, as well as how to cultivate confidence and tawakkal on the orders of Allah SWT.